2016
DOI: 10.1080/10773525.2016.1241920
|View full text |Cite
|
Sign up to set email alerts
|

The quality of work life of registered nurses in Canada and the United States: a comprehensive literature review

Abstract: Background: Workplace environment is related to the physical and psychological well-being, and quality of work life (QWL) for nurses. Objective: The aim of this paper was to perform a comprehensive literature review on nurses' quality of work life to identify a comprehensive set of QWL predictors for nurses employed in the United States and Canada. Methods: Using publications from 2004-2014, contributing factors to American and Canadian nurses' QWL were analyzed. The review was structured using the Work Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 84 publications
6
86
1
8
Order By: Relevance
“…Similar results were showed in Akter et al () 's and Moradi et al () 's studies, which mentioned that high‐income nurses had better QoWL than low‐income nurses. A comprehensive literature review also reported that a good enough income was significantly correlated with nurses' QoWL (Nowrouzi et al, ). The possible explanation of the positive association between income and QoWL is that nurses use incomes to support their family, and if they receive higher incomes, they can take good care of their parents and children, and fulfil family members' needs, so as to enjoy a better QoWL (Akter et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar results were showed in Akter et al () 's and Moradi et al () 's studies, which mentioned that high‐income nurses had better QoWL than low‐income nurses. A comprehensive literature review also reported that a good enough income was significantly correlated with nurses' QoWL (Nowrouzi et al, ). The possible explanation of the positive association between income and QoWL is that nurses use incomes to support their family, and if they receive higher incomes, they can take good care of their parents and children, and fulfil family members' needs, so as to enjoy a better QoWL (Akter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported similar results. Numerous studies have shown that the QoWL among nurses is at moderate to low level, and changes are required to improve nurses' QoWL in the current health care environment (Akter et al, ; Nowrouzi et al, ). In our study, factors affecting nurses' QoWL included job burnout, hospital level, age, income, night shift and patient‐to‐nurse ratio.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations